2021
DOI: 10.1371/journal.pcbi.1009361
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamics-driven mathematical model of first and second heart sound generation

Abstract: We propose a novel, two-degree of freedom mathematical model of mechanical vibrations of the heart that generates heart sounds in CircAdapt, a complete real-time model of the cardiovascular system. Heart sounds during rest, exercise, biventricular (BiVHF), left ventricular (LVHF) and right ventricular heart failure (RVHF) were simulated to examine model functionality in various conditions. Simulated and experimental heart sound components showed both qualitative and quantitative agreements in terms of heart so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…While early studies hypothesized that sudden tensing of ventricular muscles or cardiac valves gives rise to heart sounds, later studies tended to support the idea of vibrations of the whole cardiohemic system including valves, myocardia, blood mass and adjacent tissues as origin of heart sounds [4][5][6][7]. The recent simulation study in our group, based on the cardiohemic hypothesis, appeared quite consistent with previous observations of heart sounds in normal condition, heart failure and exercise [8]. Chapter 4 showed a higher frequency of heart sounds in patients with elevated LV filling pressure.…”
Section: Three Waves Of Heart Sound Researchsupporting
confidence: 85%
See 1 more Smart Citation
“…While early studies hypothesized that sudden tensing of ventricular muscles or cardiac valves gives rise to heart sounds, later studies tended to support the idea of vibrations of the whole cardiohemic system including valves, myocardia, blood mass and adjacent tissues as origin of heart sounds [4][5][6][7]. The recent simulation study in our group, based on the cardiohemic hypothesis, appeared quite consistent with previous observations of heart sounds in normal condition, heart failure and exercise [8]. Chapter 4 showed a higher frequency of heart sounds in patients with elevated LV filling pressure.…”
Section: Three Waves Of Heart Sound Researchsupporting
confidence: 85%
“…Moreover, computer simulation studies in our group showed that S2 splitting is a promising tool for evaluation of type and evolution of heart failure. S2 splitting interval is prolonged as LV function worsens at constant RV function, while shortened or even reversed as only RV function worsens [8]. Therefore, S2 splitting interval, used alone or combined with other heart sound components such as third heart sound, may be helpful for titration of drugs such as diuretics and beta-blocker, as well as optimization of pacemaker therapy in heart failure patients.…”
Section: Splitting Of Heart Soundsmentioning
confidence: 99%
“…The phonocardiogram is from a healthy subject with S3 in PhysioNet dataset ( Liu et al, 2016 ). The simulation is composed of simulated first and second heart sounds from a previous study ( Shahmohammadi et al, 2021 ) superposed to the simulated S3 in normal condition at rest (5 L/min)). Note the close agreement between the phonocardiogram and the simulation.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to a blood impact model, proper expressions are needed for at each time snapshot before the S3 sound can be simulated. Because CircAdapt ( Figure 1A ) proved to be a reliable software for simulation of cardiovascular mechanics and hemodynamics in various conditions ( Walmsley et al, 2015 ; Shahmohammadi et al, 2021 ), we used this software to identify the most appropriate values for our model parameters. Details about the used parameters of CircAdapt are extensively described in ( Walmsley et al, 2015 ; van Loon et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation